Proposed interior design of pets center for ABC Pets Sdn Bhd at Lot 987, Bandar Taiping, Jalan Istana Larut, 34000 Taiping, Perak / Siti Nurani Zakaria - Zakaria, Siti Nurani (Faculty of Architecture, Planning and Surveying, 2011)
This project is about to proposed a new interior design of pets centre for ABC Pets Sdn. Bhd which will be located at lot 987,Bandar Taiping , Jalan Istana Larut, Jalan Kemunting, Daerah Larut dan Matang, Perak Darul Ridzuan. The purpose of this project is to provide a new interior design for a pets centre that consists many area including animal display, pet accessories and supplies, grooming area and consultation area in order to promote ABC Pets products and services to the public especially to those people who has pet in their house. The objective of this project is to encourage and educate people to be more responsible and caring towards animals especially their pets through the pets store which will help and conduct them to take care of their pets. To complete this proposal, many research have been done by studying various person and parties related to pets centre industry either locally or internationally. For the results, several aspects related to the project are identified for enhancement and additions. It is also acknowledged that the strengths, weaknesses, opportunity and restriction of the store are important factors to ensure the sustainability of this project. Unlike the other retail store, pets centre is more uniqe because it does not only challenge the designer on how to create an interesting way to display products such as food and accessories but they also have to think about how to create a suitable and attractive display method for the animals.